Student Experience of School Screening, Brief Intervention, and Referral to Treatment. (24th March 2020) - Chadi, Nicholas; Levy, Sharon; Wisk, Lauren E.; Weitzman, Elissa R.
ABSTRACT: BACKGROUND: Screening, Brief Intervention and Referral to Treatment (SBIRT) is a clinical guideline that can help delay, prevent or reduce substance use behaviors in youth. We aimed to describe the experiences of middle and high school (MS and HS) students attending a school with an SBIRT program. METHODS: This was a survey study conducted in 2 school districts that implemented SBIRT programs prior to statewide roll‐out of mandatory school SBIRT in Massachusetts, in which students were asked about past‐year substance use and then received brief counseling by a school professional. Students in grades that received SBIRT were subsequently invited to complete an electronic questionnaire about their SBIRT experience. RESULTS: A total of 890 students were included in the study (63.7% MS, 36.3% HS). Experiences of school SBIRT were predominantly positive: 74.0% of participants reported that the information received was useful. Students who reported having used substances were less likely to agree that "schools should screen for substance use" than students who did not report substance use (AOR: 0.39, 95%CI: 0.29‐0.53). CONCLUSIONS: Most respondents found SBIRT of value, though students with past‐year substance use were less positive about the experience. More research is needed to optimize SBIRT delivery in schools.